Prof. Juozas Eretas' views on the history of Lithuanian culture: from „Tėvynės sargas" to „Naujoji Romuva" - Aldona Vasiliauskienė (Lietuvos Istorijos Studijos)
Numerous scientists and public figures contributed their share of honest, devoted work to the foundation of the independent Lithuanian state. The activities of Juozas Eretas (1896-1984), a Swiss, occupied a distinguished place among outstanding Lithuanians of interwar Lithuania. At the age of 23, Juozas Eretas arrived in Lithuania. With youthful zeal and a Western European outlook, he plunged into activities which demanded a great deal of ingenuity and devotion. As soon as he completed his work in one area, he would immediately start work in a new one. This strenuous life came to an end in 1928, due to his failing health.